The Effect of Health Promotion Using Audio Visual Media on Increasing Knowledge Children About The Risk of Overnutrition at State Primary School Plawad IV District Karawang - Indrayani, Triana (International Journal of Midwifery and Health Sciences, 2024)
Obesity occurs in Indonesia in children aged 5-12 years, as many as 18.8% are overweight and 10.8% are obese. Children who are overnourished are at high risk of obesity, which can lead to various health problems such as type 2 diabetes, hypertension, heart disease, and respiratory disorders. The level of children's nutritional knowledge is one of the factors that can affect the occurrence of obesity in children. Video is an audio-visual medium that can reveal objects and events such as real situations. Through video media, students can understand learning messages in a more meaningful way so that the information conveyed through video can be understood as a whole. This study aims to evaluate the effect of health promotion using audio-visual media on increasing children's knowledge about the risk of overnutrition at Plawad IV State Elementary School, Karawang Regency. This study used a quasi-experimental design of One Group Pretest-Posttest Only with 54 elementary school children selected through purposive sampling. The instrument used is a knowledge questionnaire. The data was analyzed using the Paired Sample T-Test. The average children's knowledge score increased from 10.13 before the intervention to 11.17 after the intervention, with a significant increase (p-value < 0.05). The Paired Sample T-Test showed a significant difference in the score before and after the promotion (p-value 0.000). Health promotion using audio-visual media significantly increased children's knowledge about the risks of overnutrition at Plawad IV State Elementary School, Karawang Regency.